Isolation and screening of potential antimicrobial metabolites from selected endophytic, marine and soil fungi in Sarawak, Malaysia - Anita, Tahir (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The emergence and re-emergence or antimicrobial resistant diseases are one of the health threatening phenomenons and become the main causative for significant mortality and morbidity in human worldwide. Fungi, on the other hand, are a renowned kingdom as important source of pharmaceutically bioactive compounds thus offers an option for controlling the spread of antimicrobial resistant pathogens. The present study aims to isolate and identify compound(s) with antimicrobial properties from fungi isolated endophytic-, marine- and soil-origin. Bioactive compounds from selected fungi cultivated in Potato Dextrose agar, Czapek Dox agar and V8 Juice agar, were extracted using hexane, dichloromethane, ethyl acetate, methanol and water solvent. The extracts bioactivities against Staphylococcus aureus, Salmonella typhi, Escherichia coli and Enterobacter aerogenes were assessed via series of bioassay-guided approach that employed diffusion, dilution and bioautography assay coupled with thin layer chromatography method. The cytotoxicity of semipure fractions were tested and the bioactive compounds were identified using gas chromatography-mass spectrometry (GC-MS). The studied fungi were identified using phenotypic and genotypic methods. In preliminary study, hexane extracts of fungi collected from three types media were found active against at least two bacteria, S. typhi and E. aerogenes. However, V8JA produced higher amount hexane thus become the main media for production of other fungi. After being screened through a series of bioassay-guided method, two hexane subfractions from fungi isolates 1C and L10.1.F3, denoted as H.1C.1.4 and H.L10.1.4, were found potentially yielding bioactive compounds. The LC50 of subfraction H.1C.1.4 was approximately 100 µg/ml while no toxicity effect was detected to Vero cells for 2 subfraction H.L10.1.4 at the same concentration. Four compounds were identified via GC-MS, two inclusive for both fractions namely 1-Nonadecanol, 3-Hexen-2-one while 1-Pentadecanol and 1-Heptacosanol were exclusive to semipure fraction H.1C.1.1.4 and H.L10.1.1.4, respectively. Using 16S rDNA partial sequence analysis, fungi 1C and L10.1.F3 were identified as Penicillium sclerotiorum. Additionally, fungi isolate AF1.4 is Penicillium simplicissimum while fungi isolates AF2.1, L12.1F1 and 2D were identified as Penicillium dipodomyicola. The present study highlights the potential of indigenous microbe in Sarawak, Malaysia as source of biologically active compounds for pharmacology.